Keabsahan Pemberhentian Perangkat Desa dalam Putusan PTUN Medan No.180/G/2020/PTUN-MDN: Kajian Hukum Administrasi dan Fiqh Siyasah - Lestari, Intan Mustika; Khalid, Khalid (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study explores the legitimacy of the dismissal of a village official as adjudicated in the Administrative Court Decision No. 180/G/2020/PTUN-MDN, analyzing the issue through the lens of Administrative Law and Fiqh Siyasah (Islamic political jurisprudence). The research addresses the central question: to what extent is the dismissal legally valid within the framework of state administrative law and Islamic governance principles? Employing a normative juridical method, this study examines statutory regulations, court documents, and relevant scholarly interpretations. The findings indicate that the dismissal violated procedural principles of good governance as stipulated in Indonesian administrative law, including principles of due process and legal certainty. Furthermore, from a Fiqh Siyasah perspective, the decision reflects a misuse of authority, contradicting the values of justice (‘adl) and public accountability (maslahah). The court's ruling to annul the dismissal reinforces the imperative of administrative justice and the ethical exercise of public power. This study concludes that harmonizing positive law with Islamic governance principles can enrich legal interpretations and strengthen the rule of law in village administration.